2021
DOI: 10.1002/mar.21576
|View full text |Cite
|
Sign up to set email alerts
|

Privacy concerns when using augmented reality face filters? Explaining why and when use avoidance occurs

Abstract: Augmented reality face filters (e.g., Snapchat) are ubiquitous in today's market. Yet, we know little about the impact of individuals' concerns for their own and others' privacy and sharing biometric facial data while interacting with such augmented reality face filters. Our study aims to uncover whether privacy concerns affect responses toward augmented reality face filter apps, as well as the underlying mechanisms of this process, specifically perceived usefulness and flow. First, a survey study shows that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 96 publications
(177 reference statements)
2
53
0
Order By: Relevance
“…The main purpose of sharing their experiences was to connect with others and be amused (Table 3). Thus, in line with previous research that has distinguished AR usage in private and public contexts (Rauschnabel, 2018), and that has shown that users of AR filters have privacy concerns (Cowan et al, 2021), the participants in the focus groups indicated that they used the filters mainly in private contexts, and they shared their experiences only with people they trust, such as friends or family ("I only share my experiences with the people I want. Sometimes I do it privately in a message and sometimes I choose from the list of my Instagram friends and share the story for a limited time"; participant 1, session 1, female; "I would never share an experience with an AR filter publicly!…”
Section: Follow-up Analysis Of Studysupporting
confidence: 81%
See 4 more Smart Citations
“…The main purpose of sharing their experiences was to connect with others and be amused (Table 3). Thus, in line with previous research that has distinguished AR usage in private and public contexts (Rauschnabel, 2018), and that has shown that users of AR filters have privacy concerns (Cowan et al, 2021), the participants in the focus groups indicated that they used the filters mainly in private contexts, and they shared their experiences only with people they trust, such as friends or family ("I only share my experiences with the people I want. Sometimes I do it privately in a message and sometimes I choose from the list of my Instagram friends and share the story for a limited time"; participant 1, session 1, female; "I would never share an experience with an AR filter publicly!…”
Section: Follow-up Analysis Of Studysupporting
confidence: 81%
“…Consistent with previous studies that have applied uses and gratifications theory to social media (Claffey & Brady, 2017;Saridakis et al, 2016), entertainment (Li et al, 2015;Ruggiero, 2000) and AR contexts (McLean & Wilson, 2019;Rauschnabel et al, 2017), this research analyzes the hedonic, utilitarian and social gratifications that users derive from interacting with AR filters (Cowan et al, 2021).…”
Section: Sourcementioning
confidence: 93%
See 3 more Smart Citations